1995
DOI: 10.1128/mcb.15.2.1079
|View full text |Cite
|
Sign up to set email alerts
|

The X Protein of Hepatitis B Virus Coactivates Potent Activation Domains

Abstract: Transactivation by hepatitis B virus X protein (pX) is promiscuous, but it requires cellular activators. To study the mode of action of pX, we coexpressed pX with Gal4-derived activators in a cotransfection system. Twelve different activators bearing different types of activation domains were compared for their response to pX. Because pX indirectly increases the amount of the activators, tools were developed to compare samples with equivalent amount of activators. We demonstrate that pX preferentially coactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 82 publications
(108 reference statements)
6
84
0
Order By: Relevance
“…HBx fused to LexA or c/EBP DNA-binding domains can transactivate the reporters harboring the responsive ciselements (9,32). HBx co-activates potent activators, including acidic activators such as VP16 and p53 as well as non-acidic activators such as E1a (33). Finally, we showed that HBx can specifically bind to RPB5, a common subunit shared by eukaryotic nuclear RNA polymerase I, II, and III, both in vitro and in vivo.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…HBx fused to LexA or c/EBP DNA-binding domains can transactivate the reporters harboring the responsive ciselements (9,32). HBx co-activates potent activators, including acidic activators such as VP16 and p53 as well as non-acidic activators such as E1a (33). Finally, we showed that HBx can specifically bind to RPB5, a common subunit shared by eukaryotic nuclear RNA polymerase I, II, and III, both in vitro and in vivo.…”
mentioning
confidence: 87%
“…Therefore an obvious question is how the HBx-RPB5-TFIIB trimeric interaction enables promoter selectivity in HBx transactivation. HBx alone does not transactivate the pGal4-CAT reporter but facilitates the activation of Gal4-VP16, suggesting that HBx acts during activated, but not basal transcription (33,63). 3 In this regard, HBx may directly or indirectly communicate with some transcriptional activators (19,20).…”
Section: Hbx Rpb5 and Tfiib May Form A Ternary Complex-mentioning
confidence: 99%
“…Huh7 cells were maintained in Dulbecco's modified Eagle's minimal essential medium as previously described. 8 Cells were seeded at about 60% confluence 4 to 6 hours before transfection, which was carried out by the CaPi method as previously described. 8 Plasmid Constructs.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were cultured and transfected as previously described (Haviv et al, 1995). About 8 h before transfection, 2610 5 cells were plated per 3.5 cm dish.…”
Section: Luciferase Assaysmentioning
confidence: 99%